Analisis Penggunaan Metode Pembelajaran Resitasi Pada Mahasiswa Akuntansi - Marlina Magdalena (Universitas Muhammadiyah Malang, 2021)
This study aims to determine the effect of applying the recitation method on the learning outcomes of Introduction to Accounting 2. The subjects in this study were Semester 2 students of the Accounting Department. This type of research is an experimental study with a nonequivalent control group design. Data analysis in this study used the one way ANOVA test. The results of this study indicate that the average value of student learning outcomes given the application of the recitation learning method is not significantly different from the application of the lecture learning method but still can improve student learning outcomes so that it can be used as a learning method in accounting.